The undercurrents of water stewardship in the Syilx Okanagan territory: Setting the stage for ethical space engagement - Maria Correia; Sarah Alexis; Marcello Glo; Shruti Suresh; Aleksandra Dulic (Social Sciences and Humanities Open)
‘Ethical space,’ as defined at the intersection of Indigenous and Western worldviews, draws attention to the unseen forces that shape cross-cultural relations. Applying ethical space as a conceptual lens, this study examines Indigenous and non-Indigenous perspectives on water stewardship in the Syilx Okanagan territory in British Columbia, Canada, with the aim of uncovering these invisible dynamics. Through qualitative inquiry with Syilx and non-Indigenous participants, we identify areas of convergence and divergence in understandings of water stewardship. We find that both groups recognized the exclusionary nature of colonial water governance. Indigenous participants emphasized inherent water rights tied to unceded territory, while non-Indigenous participants often overlooked these legal and historical dimensions. Water was framed as a sacred ‘relative’ by Syilx participants and as a ‘resource’ by non-Indigenous participants, reflecting contrasting ontologies and values. Despite these broad differences, there was consensus on the importance of building cultural competencies and addressing systemic governance inequities. Findings underscore the complexities of cross-cultural collaboration in water stewardship amidst broader political, economic, and social challenges. Future research should focus on ethical space as praxis in multi-institutional settings including the role of policy in supporting these efforts, and its potential for building new partnership models to address pressing social-ecological challenges.